Research on curriculum ideological and political design based on online and offline mixed teaching - Cheng Yulong (SHS Web of Conferences, 2023)
"Curriculum ideological and political education" is to integrate ideological and political education elements into professional courses, imperceptibly influence students' ideology and behavior, and give full play to the function of cultivating virtues and cultivating people. This paper explores ideological and political elements deeply, according to the requirements of curriculum standards, centering on teaching objectives and teaching content, carries out curriculum ideological and political design based on blended teaching mode, runs ideological and political education throughout education and teaching, implements the goal of "three-in-one education", and cultivates students' good professional quality and professional skills.